Multifunctional performance of carbon nanotubes and graphene nanoplatelets reinforced PEEK composites enabled via FFF additive manufacturing. (1st March 2020) - Arif, M.F.; Alhashmi, H.; Varadarajan, K.M.; Koo, Joseph H.; Hart, A.J.; Kumar, S.
Abstract: The study is focused on multifunctional performance of carbon nanotubes (CNT) and Graphene nanoplatelets (GNP) reinforced PEEK composites enabled via fused filament fabrication (FFF) additive manufacturing (AM) utilizing in-house nanoengineered filaments. Thermo-physical, mechanical and wear characteristics of electro-conductive PEEK nanocomposites are reported. The coefficient of thermal expansion (CTE) is found to decrease by 26% and 18% with the incorporation of 5 wt% GNP and 3 wt% CNT into PEEK polymer, respectively. The decrease in CTE provides better dimensional stability to resulting nanocomposite structures. Due to uniform dispersion of CNT and GNP in the PEEK matrix, the crystallization temperature and degree of crystallinity are both increased. The 3D printed PEEK nanocomposites reveal interfacial voids between the beads and intra-bead pores and thus exhibit lower density compared to that of the 3D printed neat PEEK. Young's and storage moduli are found to increase by 20% and 66% for 3 wt% CNT loading and by 23% and 72% for 5 wt% GNP loading respectively. However, the PEEK nanocomposites exhibit similar tensile strength to that of neat PEEK. The coefficient of friction obtained from fretting wear tests is found to decrease by 67% and 56% for 1 wt% CNT and 3 wt% GNP loaded PEEK nanocomposites, respectively and the decrease is attributed to reduced hardness and increased porosity. Multifunctional performance of carbon nanostructures reinforced AM-enabled PEEK composites demonstrated here makes them suitable for a range of applications such as orthopedics, oil and gas, automotive, electronics and space. Graphical abstract: Image 1 Highlights: The crystallization temperature and degree of crystallinity of AM-PEEK increase with the addition of carbon nanostructures. The CTE of PEEK nanocomposites decreases by 26% and 18% with the addition of 5wt.% GNP and 3wt.% CNT, respectively. Young's modulus of PEEK increases by 20% and 23% by the addition of 3wt.% CNT and 5wt.% GNP respectively. The PEEK/GNP exhibits ductile fracture with concomitant increase in strain at break and toughness relative to neat PEEK. The coefficient of friction decreases by 67% for 1wt% CNT and 56% for 3wt% GNP due to reduced hardness & increased porosity.